1979
DOI: 10.3386/w0310
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Savings and International Capital Flows

Abstract: This paper uses new statistical estimates to compare two views of international capital mobility. With perfect world capital mobility, there would be little or no relation between the amount of saving generated in a country and the domestic investment in that country. In contrast, if portfolio preferences and institutional rigidities impede the flow of long-term capital among countries, increases in domestic saving would be reflected primarily in additional domestic investment. The statistical evidence present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
262
0
20

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 397 publications
(310 citation statements)
references
References 4 publications
28
262
0
20
Order By: Relevance
“…While the former make use of the fact that in integrated financial markets rates of return on identical financial assets must be the same, the latter are based on the notion that in integrated financial markets domestic investment should not be constrained by the supply of domestic savings (Feldstein and Horioka 1980). It is a relatively common finding in the empirical literature that price measures show a greater degree of integration than quantity measures (Bayoumi 1998).…”
Section: Measuring Capital Mobilitymentioning
confidence: 99%
See 1 more Smart Citation
“…While the former make use of the fact that in integrated financial markets rates of return on identical financial assets must be the same, the latter are based on the notion that in integrated financial markets domestic investment should not be constrained by the supply of domestic savings (Feldstein and Horioka 1980). It is a relatively common finding in the empirical literature that price measures show a greater degree of integration than quantity measures (Bayoumi 1998).…”
Section: Measuring Capital Mobilitymentioning
confidence: 99%
“…In their seminal paper, Feldstein and Horioka (1980) have suggested to measure the degree of international capital mobility by looking at the correlation between domestic saving and investment:…”
Section: Measuring Capital Mobilitymentioning
confidence: 99%
“…The second bias is the famous saving-investment phenomenon first identified in Feldstein and Horioka (1980). Feldstein and Horioka demonstrated that across OECD countries, the average national saving rates over long periods are highly correlated with the averages of domestic investments.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Specifically, this alternative approach to examining the extent of capital mobility, pioneered by Feldstein and Horioka (1980) with subsequent papers by Feldstein (1983), Feldstein and Bacchetta (1991) and Feldstein (1994), focuses on measuring the correlation between domestic saving and domestic investment as an indicator of international capital mobility. Feldstein and Horioka (1980), hereafter FH, note that the fraction of an increase in domestic saving reflected in an increase in domestic investment (termed the "saving retention coefficient" in subsequent work) should be approximately one if economies are largely closed. By comparison, if capital is highly mobile internationally, domestic saving and investment should be nearly uncorrelated, as any increase in domestic saving is distributed across the world economy to maximize after-tax returns and increases in domestic investment are financed from the world supply of capital rather than from domestic saving.…”
Section: Saving and Investment Correlationsmentioning
confidence: 99%
“…By comparison, if capital is highly mobile internationally, domestic saving and investment should be nearly uncorrelated, as any increase in domestic saving is distributed across the world economy to maximize after-tax returns and increases in domestic investment are financed from the world supply of capital rather than from domestic saving. Feldstein and Horioka (1980) examined averages over five years or more of annual domestic saving and investment rates relative to GDP over the period 1960-1974 for a cross-section of 16 OECD countries. They argued that with perfect capital mobility the saving retention coefficient for a given country should roughly equal its share of the world capital stock and, in the aggregate, should be less than 0.10 for their sample of OECD countries.…”
Section: Saving and Investment Correlationsmentioning
confidence: 99%